Up‐regulation of miR‐26a promotes neurite outgrowth and ameliorates apoptosis by inhibiting PTEN in bupivacaine injured mouse dorsal root ganglia. (29th April 2015) - Cui, Changlei; Xu, Gong; Qiu, Jinpeng; Fan, Xiushuang
Abstract Local anesthetic of bupivacaine may inhibit neurite outgrowth and induce apoptosis in mouse dorsal root ganglia (DRG) neurons. In this work, we intended to investigate the functional role of microRNA 26a (miR‐26a) in regulating bupivacaine‐induced nerve injury in DRG neurons. DRG neurons were extracted from C57BL/6 mice and cultured in vitro. Bupivacaine was applied in vitro and it induced apoptosis, inhibited neurite growth, and significantly down‐regulated miR‐26a gene in DRG neurons. MiR‐26a mimic was then used to up‐regulate miR‐26a expression in DRG neurons. We found that miR‐26a up‐regulation promoted neurite outgrowth and reduced apoptosis in bupivacaine‐injured DRG neurons. Luciferase assay and Western blot confirmed that Phosphatase and tensin homolog (PTEN) was down‐stream target of miR‐26a in DRG neurons. Ectopic PTEN up‐regulation was then able to reverse the protective effect of miR‐26a overexpression on bupivacaine‐induced nerve injury in DRG neurons. Overall, this work demonstrated that miR‐26a had a functional role in regulating bupivacaine‐induced nerve injury in DRG neurons. Up‐regulating miR‐26a to suppress PTEN signaling pathway may be an effective method to protect local anesthetic‐induced nerve injury in spinal cord.